Pengujian Power 5 Volt Di Laboratorium Teknik Elektronika Politeknik Negeri Malang - Imam Saukani (UIN Sunan Kalijaga Yogyakarta, 2020)
Power supplies are generally used to supply electronic devices that require DC current (Enny, 2016). The use of a power supply in a practicum with the material